Comparison of tension band wiring method applied with k-wire or cannulated screw in mayo 2A olecranon fracture fixation: A biomechanical study mayo 2A olecranon kırık tespitinde K-teli veya kanüllü vida ile uygulanan gergi bantlama metodunun karşılaştırması: biyomekanik çalışma - KAYA, MİTHAT (My University, 2022)
© 2022, Duzce University Medical School. All rights reserved.Aim: The study aimed to compare the biomechanical stability and strength of the tension band wiring method used to treat mayo 2A olecranon fractures with Kirschner (K)-wire or cannulated screw configurations. Material and Methods: A total of 24 anatomical ulna models (Sawbones Model 1004, Pacific Research Laboratories, Vashon Island, WA) used in the study were divided into two equal groups of 12, tension band fixation with K-wire (Group 1) and tension band fixation with cannulated screw (Group 2), and groups were compared. The mechanical comparison was performed with a universal measuring machine (Shimadzu Autograph 50 kN; Shimadzu Corp). Results: Fixation methods comparison (K-wire/cannulated screw) were the main factors that determined the stability and the strength of the internal fixation. The median flexion strength of Group 1 was 107.92 (range, 94.22-121.72) N, and that of Group 2 was 109.67 (range, 105.07-113.86) N. The median varus strength of Group 1 was 100.02 (range, 83.24-102.18) N, and that of Group 2 was 76.32 (range, 68.44-78.43) N. Varus strength and stiffness were significantly higher in the K-wire group than in the cannulated screw group (both p values were <0.001). No significant differences were detected between the groups regarding flexion strength and stiffness (both p values were 0.999). Conclusion: Although no significant differences were detected between the two fixations in flexion bending cyclic loading, a significantly more stable fixation was achieved in tension banding applied with K-wire in varus bending cyclic loading. No reduction loss was detected during cyclic loading tests in either technique.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; displaced transverse olecranon fracture; Olecranon fracture fixation; tension banding